2019
DOI: 10.1111/cen.14042
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone score and bone remodelling markers identify perimenopausal women at high risk of bone loss

Abstract: Context Bone loss is accelerated in the late perimenopause and early menopause. The date of the final menstrual period cannot be stated until 1 year after it has ended, and at that time, most of the rapid bone loss phase will have elapsed. Therefore, early detection of bone loss is crucial. Objectives To evaluate the utility of bone turnover markers (BTM) to identify the women who are more likely to lose more bone mass during the transition to menopause and quantify the loss of bone quality measured by trabecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Bone turnover markers were evaluated 3 months after the fracture, which may still be influenced by the late phase of fracture healing. On another side, in healthy premenopausal women in the transition to menopause (aged 44-57) followed for 5 years, higher PINP and C-terminal telopeptide concentrations predicted lower BMD, suggesting that bone turnover markers could have potential use in identifying women at higher risk of rapid bone loss (49). Yet another recent study suggests that single bone turnover markers may not be able to identify bone loss for an individual patient (50).…”
Section: Identifying Patients At High Fracture Riskmentioning
confidence: 99%
“…Bone turnover markers were evaluated 3 months after the fracture, which may still be influenced by the late phase of fracture healing. On another side, in healthy premenopausal women in the transition to menopause (aged 44-57) followed for 5 years, higher PINP and C-terminal telopeptide concentrations predicted lower BMD, suggesting that bone turnover markers could have potential use in identifying women at higher risk of rapid bone loss (49). Yet another recent study suggests that single bone turnover markers may not be able to identify bone loss for an individual patient (50).…”
Section: Identifying Patients At High Fracture Riskmentioning
confidence: 99%
“…The estrogen deficiency-induced PMOP has a typical symptom of bone metabolic disorder, which can stimulate RANKL production to prolong the life span of osteoclasts and reduce the life span of osteoblasts ( 35 ). Hormone replacement therapy is often used to prevent or ameliorate bone loss by promoting osteocalcin gene expression ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…revealed that within 5 years of menopause, alveolar bone density loss was associated with elevated circulating levels of matrix metalloproteinase-2 (MMP-2) indicative of osteoclastic bone resorption [ 63 ]. Menopausal women were observed to have a higher level of bone resorption markers, like N-terminal propeptide of type I procollagen and CTX-l, and lower trabecular bone score, which correlated with skeletal microarchitecture deterioration [ 64 ].…”
Section: Direct Effects Of Estrogen On Bone Healthmentioning
confidence: 99%